Hukum Waris dalam Perspektif Sosio Historis, Normatif, dan Psikologis - Azzam Arfa, M Fadhil; Desrianto; Abdul Qodir Zaelani (Sharia Journal and Education Center Publishing, 2024)
ABSTRACT This study discusses the Law of Inheritance from Socio-Historical, Normative, and Psychological perspectives. The objectives of this research are, firstly, to understand the reasons why Islam regulates the division of inheritance, secondly, to determine whether the division of inheritance between men and women as stipulated in Islamic law can be considered just in the context of contemporary society, and thirdly, the impact of the division of inheritance when implemented fairly and unfairly. The research method employed in this discussion is library research conducted with Socio-Historical, Normative, and Psychological approaches. The data analysis method used is Analytical Descriptive. The findings of this research indicate that Islam regulates the division of inheritance to protect the existence of women who, in pre-Islamic times, did not have the right to inherit, so with the advent of Islamic law, women also have rights in inheritance. The division established by Islamic Law is still considered fair when viewed in the context of the present time, although the concept of 2:1 is not the primary reference. If a 1:1 division is agreed upon by each heir, then it can be considered fair if no party feels aggrieved. Fundamentally, the division of inheritance must prioritize the principle of justice, as inheritance issues are sensitive matters that can impact an individual's psychological well-being. Psychologically, an individual may develop feelings of envy and resentment if the division of inheritance is not conducted fairly, thus potentially fracturing family relationships. Keywords : Inheritance Law, Socio-Historical, Normative, Psychological ABSTRAK Penelitian ini membahas tentang Hukum Waris dalam perspektif Sosio Historis, Normatif, dan Psikologis. Adapun tujuan dari riset ini yakni, pertama, agar diketahui alasan Islam mengatur pembagian harta waris, kedua, agar diketahui apakah pembagian harta waris antara pria dan wanita yang telah ditetapkan pada hukum Islam dapat dikatakan sudah memenuhi unsur keadilan pada konteks masyarakat masa kini, ketiga, dampak dari pembagian harta waris jika dilaksanakan secara adil dan tidak adil. Metode penelitian pada pembahasan ini ialah riset kepustakaan (library research) yang dibahas dengan pendekatan Sosio Historis, Normatif, dan Psikologis. Adapun metode analisis data yang dipergunakan ialah Deskriptif Analitik. Hasil dari riset ini, jika Islam mengatur pembagian harta waris untuk melindungi eksistensi wanita yang pada masa pra-Islam tidak punya hak memperoleh harta waris sehingga dengan turunnya hukum Islam, wanita juga memiliki hak dalam harta waris tersebut. Adapun pembagian yang sudah ditetapkan Hukum Islam tetap dikatakan adil jika dikaitkan dalam konteks masa kini, akan tetapi konsep 2:1 tidak menjadi acuan utama. Jika pembagian 1:1 disepakati oleh masing-masing ahli waris, maka bisa dinyatakan adil jika tidak ada pihak yang merasa dirugikan. Pada dasarnya, pembagian harta waris harus mengedepankan prinsip keadilan, karena masalah harta adalah hal yang sensitive yang dapat berdampak pada psikologis seseorang. Secara psikologis, seseorang dapat menimbulkan rasa iri dan dengki jika pembagian harta waris tidak dilaksanakan secara adil, sehingga dapat memecahkan hubungan kekeluargaan. Kata kunci: Hukum Waris, Sosio Historis, Normatif, Psikologis